PEMANFAATAN SUMBER BELAJAR BERBASIS LINGKUNGAN PADA PEMBELAJARA LARUTAN ELEKTROLIT DAN NON ELEKTROLIT MENGGUNAKAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN MOTIVASI, PEMAHAMAN KONSEP, DAN KETERAMPILAN PROSES SAINS SISWA - Ummi Mahmudah; Arif Sholahuddin (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. This study was classroom action research (CAR), which consists of two cycles. Research conducted in the Class X SMA Negeri 8 Banjarmasin, while the observed factors include teacher activities, student activities, psychomotor, affective, motivation, understanding of concepts, and science process skills. The results showed an increase from the first cycle to the second cycle which includes students 'learning motivation of the worth category to good category, understanding students' concept, 64.60% to 84.57%, science process skills of students from less skilled category to skilled category, as well as the students gave a positive response, 94.28% to this learning.Keywords: learning resource-based environment, guided inquiry learning model, electrolyte and non electrolyte solution, motivation, understanding of concepts, and science process skills.